Optimizing Management of Early Childhood Education in Community Empowerment - Firdaus, Nunu Mahmaud; Ansori, Ansori (Universitas Negeri Semarang, 2019)
Considering the low level of public knowledge about the importance of Early Childhood Education and the low quality of management and the lack of infrastructure (in the form of APE) as well as the many assumptions from the public that Early Childhood Education can only be reached by economically capable people causing lack of motivation to involving their children in the Early Childhood Education program, it is deemed necessary to carry out a study on the optimization of the management of non-formal Early Childhood Education programs held in the community, such as the SPS Early Childhood Education Cempaka which operates in RW 09 Ciwaruga Village, Bandung Regency West. Through the application of qualitative methods with a case study approach, the results of this study reveal that the management process still does not meet the standards required by the government as the organizing program for the Similar Early Childhood Education Unit (SPS) program. Therefore, the manager must be able to define and find ways to achieve all the objectives set through the effective implementation of management functions of Early Childhood Education management.